2011
DOI: 10.1111/j.1532-849x.2011.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Irrigant, Dowel Type, and Root-Reinforcing Material on Fracture Resistance of Thin-Walled Endodontically Treated Teeth

Abstract: Thin-walled roots that had the smear layer removed with lactic acid and that were then lined with composite resin had a higher fracture resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 52 publications
1
30
0
6
Order By: Relevance
“…This may be attributed to the various levels of remaining tooth structure used, whereas in our study there was no remaining tooth structure. However, in a study in which similar materials and failure protocol were used to compare titanium prefabricated and quartz fiber posts, the values of fracture resistance of the studied groups were as high as in the previous studies, approximately 500 N. 23 Similarly, in this current study, these groups showed similar fracture resistance but at much lower fracture values, possibly caused by the combination of cyclic loading and thermal fatigue that was not present in the previous study. Another study, in which the same post systems were used (ParaPost XP and Parapost XH) in teeth with 1 mm of remaining tooth structure, showed more comparable results, 207.3 (13.5) N for the cast post and core group and 284.7 (16.4) N for the titanium prefabricated post group.…”
mentioning
confidence: 44%
See 1 more Smart Citation
“…This may be attributed to the various levels of remaining tooth structure used, whereas in our study there was no remaining tooth structure. However, in a study in which similar materials and failure protocol were used to compare titanium prefabricated and quartz fiber posts, the values of fracture resistance of the studied groups were as high as in the previous studies, approximately 500 N. 23 Similarly, in this current study, these groups showed similar fracture resistance but at much lower fracture values, possibly caused by the combination of cyclic loading and thermal fatigue that was not present in the previous study. Another study, in which the same post systems were used (ParaPost XP and Parapost XH) in teeth with 1 mm of remaining tooth structure, showed more comparable results, 207.3 (13.5) N for the cast post and core group and 284.7 (16.4) N for the titanium prefabricated post group.…”
mentioning
confidence: 44%
“…3 Using teeth with no remaining tooth structure allowed a direct comparison among the post systems without the influence of the ferrule effect. This allowed direct load transfer to the root, and despite being previously used for compromised teeth, 23 it may be a limitation of the study. Also, a gentle air stream was used to evaporate the accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 99%
“…При усложнении экспериментальной модели и изготовлении культи и ко-ронки акцент смещается с собственно прочности корня на тип восстанавливающей его штифтовой системы, каче-ство ее изготовления, прилегания и влияющие на это ин-дивидуальные анатомические особенности зуба [2]. Кро-ме того, выбранная нами экспериментальная модель по-зволила получать вертикальные трещины, а не косые пе-реломы в коронковой трети корня.…”
Section: экспериментально-теоретический разделunclassified
“…Было показано, что ирригация корне-вых каналов 5% раствором гипохлорита натрия не влияет на прочность зубов. В то же время после их обработки рас-твором молочной кислоты (10 и 20%) и ЭДТА (15%) их прочность снижалась [2].…”
unclassified
“…Restoratif tedavilerin klinik başarısı, dişin yüzey miktarı, dişin koronal kısmının restorasyona uygun oluşu, dişin çiğneme kuvvetlerine karşı dayanıklılığı ve stresin kemik ve periodontal ligament üzerinde dağılımı gibi birçok faktöre bağlıdır (1,2). Bilindiği üzere periodontal ligamentin kalınlığı 0.1 ile 0.3 mm arasında değişmektedir.…”
Section: Introductionunclassified